2018
DOI: 10.1186/s12895-018-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary and multiprofessional outpatient secondary individual prevention of work-related skin diseases in the metalworking industry: 1-year follow-up of a patient cohort

Abstract: BackgroundIn Germany, work-related skin diseases are predominant within the spectrum of reported occupational diseases. Metal workers are among the high-risk professions. Offering effective prevention programs to affected patients is of utmost importance to avoid deterioration of the disease and job loss. We conducted a 1-year follow-up in patients who participated in a multidisciplinary, complex outpatient prevention program representing a standard procedure of patient care by the respective statutory acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 48 publications
(89 reference statements)
3
32
0
Order By: Relevance
“…[3][4][5]7 A recent study in 94 MWs with WRSD from Germany showed that 1 year after taking part in a SIP, the disease severity was significantly lower than at baseline and 88.3% had remained in their profession. 6 The TIP is offered to patients with severe symptoms refractory to secondary prevention measures, whereas the SIP targets patients with early and/or mild symptoms of the disease, shortly after notification of the statutory accident insurances. Accordingly, the disease severity was significantly lower and its prior duration significantly shorter in SIP patients than in TIP patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5]7 A recent study in 94 MWs with WRSD from Germany showed that 1 year after taking part in a SIP, the disease severity was significantly lower than at baseline and 88.3% had remained in their profession. 6 The TIP is offered to patients with severe symptoms refractory to secondary prevention measures, whereas the SIP targets patients with early and/or mild symptoms of the disease, shortly after notification of the statutory accident insurances. Accordingly, the disease severity was significantly lower and its prior duration significantly shorter in SIP patients than in TIP patients.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with other studies, irritant contact dermatitis was the most common diagnosis in both groups. 6,10 Atopic skin diathesis and AD, which are associated with impaired skin barrier function, are well-recognized risk factors for developing WRSDs, particularly irritant contact dermatitis. 18,34,35 In the present study, an atopic hand eczema component and AD observed at body areas other than the hands were significantly more common in TIP patients than in SIP patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first weeks of apprenticeship, they received a structured 90‐minute training on causes and prevention of work‐related HE consisting of an oral, interactive, and dialogue‐oriented presentation by an experienced health educator, combined with hands‐on practical exercises on correct use of protective gloves, barrier creams, and skin care products. This training was based on seminars regularly conducted by the University of Osnabrück for patients with work‐related HE and previous studies with adjustments for MWAs . The maximum number of MWAs receiving the training at a time was 25.…”
Section: Methodsmentioning
confidence: 99%